Plan estratégico para mejorar el posicionamiento comercial de la empresa construcciones mecánicas Albán “CMA” en la ciudad de Latacunga en el periodo 2014-2019 - Chicaiza Vaca, Lesly Gissela (2015)
This research work is based on a field study Applied Business Mechanical Construction Alban. Cía. Ltda., In order to conduct a situational analysis macro and micro environment to determine the level of commercial positioning of the company. It began in the development of the theoretical framework focusing on topics such as management, process management, strategic plan, market research, segmentation and positioning….